ChemInform Abstract: Synthesis and in vitro Antimycobacterial and Isocitrate Lyase Inhibition Properties of Novel 2‐Methoxy‐2′‐hydroxybenzanilides, Their Thioxo Analogues and Benzoxazoles. Issue 13 (18th March 2013) - Kozic, Jan; Novotna, Eva; Volkova, Marie; Stolarikova, Jirina; Trejtnar, Frantisek; Wsol, Vladimir; Vinsova, Jarmila
Abstract All newly synthesized compounds are evaluated for their in vitro antimycobacterial activities as well as for their isocitrate lyase (ICL) inhibition properties.